2018
DOI: 10.1093/jas/sky304
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by feed interaction for feed efficiency and growth performance traits in pigs1

Abstract: A major objective of pork producers is to reduce production cost. Feeding may account for over 75% of pork production costs. Thus, selecting pigs for feed efficiency (FE) traits is a priority in pig breeding programs. While in the Americas, pigs are typically fed high-input diets, based on corn and soybean meal (CS); in Western Europe, pigs are commonly fed diets based on wheat and barley with high amounts of added protein-rich coproducts (WB), e.g., from milling and seed-oil industries. These two feeding scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…The average production performances (ADG, BF and FCR) of the test pigs in this study from 2011 to 2016 were 925 g, 9.9 mm and 2.5, respectively. Similar test station performances have also been reported in other recent studies in different breeds, for example, Jiao, Maltecca, Gray, and Cassady (), Do et al (), Bahelka, Tomka, Bucko, and Hanusova () and Godinho et al (). Thus, Finnish Yorkshires have similar growth performance than other recently studied pig breeds.…”
Section: Discussionsupporting
confidence: 88%
“…The average production performances (ADG, BF and FCR) of the test pigs in this study from 2011 to 2016 were 925 g, 9.9 mm and 2.5, respectively. Similar test station performances have also been reported in other recent studies in different breeds, for example, Jiao, Maltecca, Gray, and Cassady (), Do et al (), Bahelka, Tomka, Bucko, and Hanusova () and Godinho et al (). Thus, Finnish Yorkshires have similar growth performance than other recently studied pig breeds.…”
Section: Discussionsupporting
confidence: 88%
“…The genetic correlation of 0.50 for residual feed intake indicated the presence of a genotype × environment (diet) interaction, and the authors concluded that the dependency of residual feed intake on the feeding regimen may have serious implications when selecting animals in the beef industry. Similarly, commercial pigs are typically fed high-input diets based on corn and soybean meal in the Americas, whereas they are commonly fed diets based on wheat and barley with high amounts of added protein-rich coproducts in Western Europe (Godinho et al, 2018). Results by Godinho et al (2018) showed that selecting pigs under a different diet from the diet used for growing-finishing performance could severely compromise residual energy intake during the grower phase.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, commercial pigs are typically fed high-input diets based on corn and soybean meal in the Americas, whereas they are commonly fed diets based on wheat and barley with high amounts of added protein-rich coproducts in Western Europe (Godinho et al, 2018). Results by Godinho et al (2018) showed that selecting pigs under a different diet from the diet used for growing-finishing performance could severely compromise residual energy intake during the grower phase.…”
Section: Discussionmentioning
confidence: 99%
“…The amount and type of feed offered, energy supply, animal sex and body weight, season of rearing, etc. interact with the genetic background to influence variations in RFI and other FE traits [18]. Likely, this adds to the difficulty to find common candidates to explain and predict FE.…”
Section: Introductionmentioning
confidence: 99%